Publish Or Perish: Scholarly Publishing Challenges In Africa - Leila Bellour (The Journal of Studies in Language, Culture and Society, 2024)
Researchers are judged by their scholarly publishing and the quality of the journals where they publish their manuscripts. Academic publishing is very essential for their promotion and the university’s accreditation. The terrible reality is that academic research and publishing do not conform to the high standards. Thus, compared with their Western counterparts, the African universities are lagging behind. My paper evinces the problems encountered by researchers in their academic research and the factors that challenge scholarly publishing. This topic is worth dwelling on because it may hold the solutions to the problems of scholarly publishing in Africa. The paper ends with some suggestions and recommendations for improving the quality of academic research and publishing.